Thermal/stress analysis of a failed fire-tube heater treater. (October 2020) - Zangeneh, Sh.; Bakhtiari, R.; Veysi, F.; Jowzi, M.
Highlights: The fire tube failed due to thermal stress. The increasing of scale layer thickness increased thermal stress in U-turn section. Sulfide inclusions had significant role in the failure. Lower supporters are important in stress distribution in the fire tube. Abstract: The aim of this research is to understand the reason of failure in a fire-tube heater-treater using finite element method (FEM). The fire tube, made of ASTM A516 G70 steel, failed after 15 years in service under continues operation. A crack in the fire tube at U-turn section started on the outer diameter (OD) surface of the heat-affected zone (HAZ) and consequently led to leakage. In this investigation, the results obtained from the experimental analysis were summarized, and finite element (FE) models were employed to predict thermal stress during continues service operation. It was observed that increasing the thickness of the scale layer, increased the temperature gradient in the fire tube and therefore caused severe thermal stress concentration at the U-turn section. The fractographic studies showed that Manganese sulfide (MnS) inclusion played an important role in the crack formation.